Tingkat Pengetahuan Masyarakat Terhadap Tayangan Iklan Anlene di Televisi Versi “Usia Bukan Halangan” - Dhefine Armelsa; Devy Putri Kussanti; Faqihar Risyan (Universitas Bina Sarana Informatika, 2023)
This paper is intended as a research report that the author conducted in the community of RT 001 RW 012, Cawang sub-district, East Jakarta to complete a thesis, which concerns Anlene Milk Advertisements on television. Writing This research discusses everything the author does to analyze the level of public knowledge of Anlene advertisements on television, namely from chapter 1 which contains the background of the research problem, chapter 2 which deals with theoretical frameworks, chapter 3 which contains research methods, chapter 4 which deals with the discussion up to Chapter 5 is in the form of conclusions and suggestions. Based on research conducted by the author, it can be concluded from the results of this study that the level of knowledge of the RT 001 RW 012, Cawang sub-district, East Jakarta based on the three dimensions of the Knowledge variable, namely Awareness, How to Knowledge, Principal Knowledge is High. Keywords: Awareness, How to Knowledge, Principal Knowledge